SIKAP BERBAHASA INGGRIS MASYARAKAT KELOMPOK SADAR WISATA (POKDARWIS) “WARISAN PUSAKA” DALAM MEMBERIKAN LAYANAN KEPADA WISATAWAN DI DESA WISATA MUNGGU MENGWI BADUNG, BALI - I Ketut Murdana (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
The research in general aimed at studying or analyzing English language attitude of tourism conciousness community “Warisan Pusaka” in providing services to the guests at Tourism village of Munggu Mengwi, Badung, Bali. Specifically the research aimed at revealing and analyzing the English language attitudes, which are: positive, negative and neutral language attitudes of the tourism conciousness community of “Warisan Pusaka” at Munggu Tourism Village, Mengwi, Badung, Bali. The primary research data are directly collected from the research informant during the interview procesess and also from the research questionnaires. The informant were selected using purposive, snowball and abundant sampling techniques with the total numbers of 30 samples are analysed. The research revealed that 0,88% of the informan showed positive language attitude, from the genders points of view the number of 0,76% and 0,25% showed positive language attitude. Based on the profession 0,25% of the informan showed positive attitude.